Direct Tensile Test Method for Shotcrete - Oleg V. Kabancev; Oleg A. Simakov (Buildings)
This study substantiates the need for direct tensile strength testing of shotcrete and fiber-reinforced shotcrete, rather than relying on indirect methods, to accurately reflect material performance under biaxial stress conditions when used for structural reinforcement. Experiments on field specimens confirmed that tensile strength values derived through direct testing differ significantly from those calculated based on compressive strength. The study presents a new testing methodology with optimized specimen dimensions (32, 40, 50, and 82 mm diameter cylinders with length-to-diameter ratios of 3.0) to mitigate eccentricity effects, ensuring normal-section failure. Results show that tensile strength values for fiber-reinforced shotcrete with brass-coated fibers (13–15 mm length, 0.3–0.5 mm diameter, 30 kg/m3 dosage) reached 68 MPa, compared to 60 MPa for standard shotcrete, while basalt-fiber reinforcement (6 mm length, 1% by weight) resulted in 42 MPa. The initial modulus of elasticity for unreinforced shotcrete was 280 × 103 MPa, with fiber reinforcement slightly increasing this value to 287 × 103 MPa. The findings support a direct approach to testing, providing a foundation for developing predictive methodologies for fiber-reinforced shotcrete properties based on reinforcement type and dosage. These results are essential for applications such as seismic strengthening, where accurate tensile characteristics are critical for performance under dynamic loading.